TRANSFORMASI KESEHATAN UNTUK INDONESIA MAJU MELALUI GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) KE REMAJA PUTRI DI MAN 4 KEDIRI - Nuraisya, Wahyu (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Germas, or Movement for a Healthy Living Society, dealing with health problems is still a serious challenge in Indonesia. The transformation of an increasingly modern society's lifestyle into one of Germas' basic principles for reproductive health is of paramount importance, especially for adolescents. The purpose of this activity is to successfully promote the Germas which has been promoted by the government, especially to teenage princesses. The target of this devotional activity is a teenage daughter of 100 people in MAN 4 Kediri. The method of activity is in the form of morning exercises together and the administration of blood supplement tablets to teenage daughters. As for the results achieved in this activity, teenagers 100 % follow the morning exercise together and 2 teenage girls initially do not want to take blood supplements tablets, but in the end, 100 % of teenagers drink blood tablets. Morning gymnastics and blood supplementation pills are some of the gifts that are given to the young girls' community to maintain reproductive health in teenage girls so that they can support the optimization of the health of teenage daughters in Indonesia.